Investigating the Role of Von Willebrand Factor in Regulating Macrophage Biology and Innate Immunity - DRAKEFORD, CLIVE (Trinity College Dublin. School of Medicine. Discipline of Haematology, 2019)
The plasma multimeric glycoprotein von Willebrand factor (VWF) plays a critical role in primary haemostasis by tethering platelets to exposed collagen at sites of vascular injury. Recent studies have suggested that VWF may play an important role in regulating inflammatory responses. In particular, data from clinical trials have demonstrated that patients with reduced plasma VWF levels are significantly protected against ischemic heart disease and stroke. In addition, studies performed in a number of animal inflammation models (including, sepsis, dermatitis, stroke and malaria) have reported a pathogenic role for VWF. Critically however, the biological mechanisms through which VWF exerts its immuno-modulatory effects remain poorly understood. Interestingly, recent studies have shown that VWF can bind to macrophages. Furthermore, a number of specific macrophage receptors have been implicated in regulating the binding of VWF, including the low density lipoprotein receptor-related protein-1 (LRP1), scavenger receptor class A member 1 (SR-A1) and macrophage galactose-type lectin (MGL). Given the importance of macrophages in regulating innate immune responses, we hypothesized that VWF binding might influence macrophage biology and thereby impact upon inflammatory responses. Initially, we confirmed that full-length VWF, as well as a series of truncated VWF fragments, could bind to macrophages. This binding was observed under static conditions, but was significantly enhanced in the presence of ristocetin. Importantly, we further showed that VWF binding to macrophages triggered significant pro-inflammatory signalling and activation. Treatment of both human and murine macrophages with VWF resulted in activation of MAP-kinase and NF-kB pathways, leading to the enhanced expression of a panel of pro-inflammatory cytokines. Macrophages treated with VWF adopted a M1 phenotype, confirmed by cell surface marker expression and inflammasome activation. Additionally, we observed that VWF altered functional aspects of macrophage biology such as phagocytosis and chemotaxis capacity. In order for macrophages to generate a pro-inflammatory response, significant metabolic changes must occur. In particular, a marked upregulation in macrophage glycolysis is required to meet the need to rapidly generate increased energy. In keeping with the pro-inflammatory effects of VWF-binding, we observed significant effects upon macrophage immuno-metabolism. Thus, VWF treatment significantly elevated macrophage glycolysis and induced modifications in mitochondrial biogenesis. Importantly however, in contrast to LPS, these pro-inflammatory changes induced by VWF were strictly time-dependent. The ability of damage and pattern associated molecular pathways to promote macrophage glycolysis has been attributed to HIF-1α activation. We demonstrated that the VWF time-dependent glycolytic changes included HIF-1α activation. Furthermore, we demonstrated that the VWF pro-inflammatory effect was at least in part mediated though LRP1 signalling Finally, we established a novel direct link between VWF/LRP1 dependent p38 signalling and early glycolytic changes, as inhibition of p38 fully attenuated VWF dependent glycolysis and HIF-1α activation. Cumulatively, our novel findings define an entirely novel biological role for VWF in modulating macrophage function, and thereby establish a novel link between primary haemostasis and innate immunity.
APPROVED
Keywords: Von Willebrand factor; Haemostasis; HIF-1α; Immunity